Ectopic mineralization of articular cartilage in the bullfrog Rana catesbeiana and its possible involvement in bone closure - Felisbino, S. L.; Carvalho, H. F. (Springer, 2002)
Mineralization of the articular cartilage is a pathological condition associated with age and certain joint diseases in humans and other mammals. In this work, we describe a physiological process of articular cartilage mineralization in bullfrogs. Articular cartilage of the proximal and distal ends of the femur and of the proximal end of the tibia-fibula was studied in animals of different ages. Mineralization of the articular cartilage was detected in animals at 1 month post-transformation. This mineralization, which appeared before the hypertrophic cartilage showed any calcium deposition, began at a restricted site in the lateral expansion of the cartilage and then progressed to other areas of the epiphyseal cartilage. Mineralized structures were identified by von Kossa's staining and by in vivo incorporation of calcein green. Element analysis showed that calcium crystals consisted of poorly crystalline hydroxyapatite. Mineralized matrix was initially spherical structures that generally coalesced after a certain size to occupy larger areas of the cartilage. Alkaline phosphatase activity was detected at the plasma membrane of nearby chondrocytes and in extracellular matrix. Apoptosis was detected by the TUNEL (TDT-mediated dUTP-biotin nick end-labeling) reaction in some articular chondrocytes from mineralized areas. The area occupied by calcium crystals increased significantly in older animals, especially in areas under compression. Ultrastructural analyses showed clusters of needle-like crystals in the extracellular matrix around the chondrocytes and large blocks of mineralized matrix. In 4-year-old animals, some lamellar bone (containing bone marrow) occurred in the same area as articular cartilage mineralization. These results show that the articular cartilage of R. catesbeiana undergoes precocious and progressive mineralization that is apparently stimulated by compressive forces. We suggest that this mineralization is involved in the closure of bone extremities, since mineralization appears to precede the formation of a rudimentary secondary center of ossification in older animals.
Keywords: alkaline phosphatase; chondrocyte; hydroxyapatite; extracellular matrix; mechanical loading; ossification; Rana catesbeiana (Anura)